The Power of the Story Writing Disasters in Haiti and the Circum-Caribbean - Joos, Vincent; Munro, Martin; Ribó, John (Berghahn Books, 2023)
A cross-disciplinary volume that combines and puts into dialogue perspectives on disasters, this book includes contributions from anthropology, history, cultural studies, sociology, and literary studies. Offering a rich and diverse set of arguments and analyses on the ever-relevant theme of catastrophe in the circum-Caribbean, it will encourage debate and collaboration between scholars working on disasters from a range of disciplinary perspectives.